Extraction of Plutonium with N-Benzoyl-Phenyl-Hydroxylamine - Cristallini, Osvaldo; Dupetit, Gustavo Alberto; Flegenheimer, Juan (Elsevier BV, 1966)
Fil: Cristallini, Osvaldo Comisión Nacional de Energía Atómica; Argentina